The Effectiveness of Prenatal Yoga on Pregnant Women’s Sleep Quality in Third Trimester - Hafid, Rachmi Nurul Hidayat (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
A pregnancy gives physiological and psychological changes in the body of pregnant women, including the resting patterns. Rest is an essential human need, if it is not fulfilled will causing a discomfort and pregnant women will be difficult to start or maintain sleep. One of the treatments that can be done to improve sleep quality is prenatal yoga. The purpose of this study was to analyze the effectiveness of prenatal yoga on sleep quality of third trimester of pregnant women. The research method used is pre-experiment one group pretest-posttest design, with total sampling and got 30 respondents of third trimester of pregnant women who meet the inclusion criteria. The research instrument used the Pittsburgh Sleep Quality Index (PSQI) then the data was analyzed with Wilcoxon Signed Rank Test and got Z-score -5.292 with ρ value 0.0001 (less than 0.05) so it can be concluded that H0 is rejected, which means that there is an effectiveness of prenatal yoga on sleep quality of third trimester of pregnant women. Practicing prenatal yoga regularly can keep the mind and body relaxed, so the pregnant women can sleep comfortably